(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
This article analyzes the views of representatives of the political ideology of neoconservatism in the field of foreign policy. In particular, the reasons for the formation of neoconservatism in the USA and the approaches of neoconservatism theorists aimed at justifying the new conservative ideology are discussed.